System model of ergatic functioning of avionic logic dynamic complex - Воробьев, В. М.; Джиджора, Н. П.; Рутов, А. М.; Доброгорская, Ю. В.; Воробьева, М. В. (Proceedings of National Aviation University (archive), 2000)
Formulated, in the proposed mathematical model of ergatic functioning of the complex "crew- aircraft-environment", is aggregate of system requirements to the quality, resources and dynamic processes. Introduced are limitations in the form of resources: technical and methodological, set of functionals, operators of algorithm structures, condition of complex functioning and its logic of operation, conditions of agreement of algorithm structures and logic of problems. Formulated is the condition of system optimization in relation to aim indexes and properties created by integrated automized system of control. Constructed is the criteria "tree" of system efficiency of logic dynamic complex functioning. The model extends to wide range of avionic stuctures